Deflection into irregularity? The (un)intended effects of restrictive asylum and visa policies - Czaika, M; Hobolth, M (International Migration Institute, 2014)
Recent research into the impact of restrictive immigration and asylum policies has found a considerable deterrence effect reducing the number of persons claiming asylum, that is as rules and procedures are tightened fewer applications are received. However, restrictive asylum policy might also push potential and rejected applicants into an irregular status. This paper investigates to what extent the deterrence effect of asylum policy is counterbalanced by such a 'deflection into irregularity’. We analyse this question drawing on a new large dyadic dataset detailing asylum and visa policy as well as forced and irregular migrant flows to 29 European states in the period 2001 to 2011. We find that restrictive asylum policy does, as expected, reduce the number of persons claiming protection. But there is also a significant deflection dynamic at work. Our estimates suggest that a ten percent increase in asylum rejections raises the number of (apprehended) irregular migrants by on average about three percent, and similarly, a ten percent increase in short-stay visa rejections leading to a five percent increase in irregular migration.